2021
DOI: 10.1083/jcb.202009197
|View full text |Cite
|
Sign up to set email alerts
|

A global chromatin compaction pathway that represses germline gene expression during starvation

Abstract: While much is known about how transcription is controlled at individual genes, comparatively little is known about how cells regulate gene expression on a genome-wide level. Here, we identify a molecular pathway in the C. elegans germline that controls transcription globally in response to nutritional stress. We report that when embryos hatch into L1 larvae, they sense the nutritional status of their environment, and if food is unavailable, they repress gene expression via a global chromatin compaction (GCC) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(60 citation statements)
references
References 28 publications
2
55
0
Order By: Relevance
“…Moreover, using an adjusted p-value cutoff of 0.05, we found 316 differentially expressed genes (DEGs) in the top-2/capg-2 RNAi samples, with 144 of them upregulated and 172 downregulated (Figure 5B, Supplemental Table 1). The fact that more than half of the DEGs are downregulated was surprising, given the repressive nature of TOP-2 and condensin II (Belew et al, 2021; Swygert et al, 2019). A possible cause for this could be the misexpression of repressor genes due to loss of TOP-2 and condensin II which, in turn, would result in the downregulation of the genes in our experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, using an adjusted p-value cutoff of 0.05, we found 316 differentially expressed genes (DEGs) in the top-2/capg-2 RNAi samples, with 144 of them upregulated and 172 downregulated (Figure 5B, Supplemental Table 1). The fact that more than half of the DEGs are downregulated was surprising, given the repressive nature of TOP-2 and condensin II (Belew et al, 2021; Swygert et al, 2019). A possible cause for this could be the misexpression of repressor genes due to loss of TOP-2 and condensin II which, in turn, would result in the downregulation of the genes in our experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Later, at the 100-cell stage, the primordial germ cell (PGC) P 4 divides to form the Z2 and Z3 PGCs, and transcription is activated (Nakamura and Seydoux, 2008; Robertson and Lin, 2015). Z2/Z3 remain transcriptionally active as the embryo hatches; however, if the emerging L1 larvae are placed in an environment lacking food, then Z2/Z3 globally repress transcription (Wong et al, 2018; Belew et al, 2021). Transcriptional repression in Z2/Z3 is mediated by a collaboration between topoisomerase II (TOP-2), the condensin II complex, and components of the heterochromatin pathway, and is coupled to a dramatic compaction of PGC chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…What are the mechanisms employed by cells to shut down transcription in response to environmental cues? In this issue of JCB , Belew et al identify a new pathway, active through late embryogenesis and L1, that senses food shortage and mediates whole genome compaction, leading to transcriptional repression in germ cells ( 4 ).…”
mentioning
confidence: 99%
“…Yet, how the two processes work together is unclear. Importantly, the authors showed that condensin II and TOP-2 are required for the high levels of H3K9me2/3 and HPL-2 observed in the Z2/Z3 cells during starvation-induced genome compaction ( 4 ). Furthermore, the authors report that depletion of both condensin/TOP-2 and heterochromatin pathways lead to activation of transcription, connecting genome compaction to transcriptional repression.…”
mentioning
confidence: 99%
See 1 more Smart Citation